Evolution of ELMs, pedestal profiles and fluctuations in the inter-ELM period in NBI- and ECH-dominated discharges in DIII-D. (13th April 2021) - Banerjee, Santanu; Mordijck, S.; Barada, K.; Zeng, L.; Groebner, R.; Osborne, T.; Rhodes, T.L.; Snyder, P.B.; Grierson, B.; Diallo, A.
Abstract: In DIII-D, it has been observed that ELM frequency decreases by 40% and ELM spacing becomes more regular in time when heating is changed from pure neutral beam injection (NBI) to predominantly electron cyclotron heating (ECH) in ITER similar shape plasmas. In comparison with the pure NBI discharges, pedestal fluctuations in magnetics and density increase in the ECH-dominated discharges. Recovery of the pedestal profiles like electron density ( n e ), temperature ( T e ) and pressure ( p e ) shows marked differences for these two heating schemes. Average profiles in the last 30% of the ELM cycle show higher T e, lower n e, and similar p e at the pedestal top for the ECH discharge when compared to the NBI discharge. The gradient of T e (∇ T e ) is also steeper at the pedestal in the ECH discharge. Magnetic fluctuations show three distinct modes at 13–116 kHz in the ECH discharges only. n e fluctuations show two modes evolving in the inter-ELM period of the ECH discharge, a low-frequency (400 kHz) quasi-coherent mode (LFQC) and high-frequency (∼2 MHz) broadband (HFB) fluctuations. Evolution of these modes has marked correspondence with the inter-ELM ∇ T e recovery. A sharp decrease in the D α baseline is observed whenever the LFQC weakens and the HFB grows, prior to each large ELM. Transport coefficients obtained from TRANSP show that MTM and/or TEM are plausible candidates for the observed fluctuations. Linear gyrofluid simulation (TGLF) corroborates this characterization. TGLF shows that the linear growth rate of the most dominant mode peaks at ion-scale ( k θ ρ s ∼ 0.4) at the pedestal steep gradient and the frequency is in the electron diamagnetic direction. It is proposed that increased fluctuations in the ECH-dominated case, due to increased ∇ T e, caused an increase in fluctuation-driven transport in the pedestal and slowed the pedestal recovery between ELMs, leading to a reduction in the ELM frequency.